Food Safety: Recommendations for Determining Doneness in Consumer Egg Dish Recipes and Measurement of Endpoint Temperatures When Recipes Are Followed - Godwin, S.; Maughan, Curtis; Chambers, Edgar, IV (My University, 2017)
Many consumers do not follow recommended food safety practices for cooking egg dishes, such as pies, quiches, and casseroles, potentially leading to foodborne illnesses such as Salmonellosis. The United States Department of Agriculture (USDA) recommends cooking egg mixtures until the center reaches 71 degrees C (160 degrees F). The objectives of this study were to determine what endpoint temperature information consumers receive from egg dish recipes, and if recipes would lead to safe temperatures when followed. Egg dish recipes (n = 226) from 65 websites, 50 cookbooks, and nine magazine titles (multiple issues of each) were analyzed. Time was the most frequently used indicator, given in 92% of the recipes, with 15% using only time. Other indicators included: set (89), browned (76), clean toothpick/knife (60), puffed (27), and jiggled (13). Only two recipes indicated final endpoint temperatures. Three recipes (a pie, a quiche, and an egg casserole) were chosen and prepared in triplicate to see if they would reach recommended temperatures. The pie and quiche were still liquid at 71 degrees C, and were well over the recommended temperature when cooked according to instructions, but the egg casserole was not consistently above 71 degrees C, when the recipe instructions indicated it was done and the center was light brown and "jiggled" This research indicates that consumers are not receiving information on endpoint temperatures in egg recipes, but the likelihood of foodborne illness is low since most dishes probably be cooked past the recommended temperature before the consumer considers them done unless there are many inclusions that may absorb liquid and reduce the appearance of liquid in the dish.
Citation: Godwin, S., Maughan, C., & Chambers, E. (2016). Food Safety: Recommendations for Determining Doneness in Consumer Egg Dish Recipes and Measurement of Endpoint Temperatures When Recipes Are Followed. Foods, 5(3), 10. doi:10.3390/foods5030045
Keywords: Consumer Food Safety; Egg Dishes; Temperature Recommendations; Salmonella-Enteritidis; Inactivation; Resistance